Gambaran Karakteristik Nyeri Kronik Paska Operasi pada Pasien Rawat Jalan di Poli Bedah dan Poli Obstetri dan Ginekologidi RSU di Medan - Ritonga, Nahly Bayo Anggito; Chalil, Muhammad Jalaluddin Assuyuthi (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Chronic pain is pain that persistent and will continue beyond the proper healing time, there are two time points used in daily practice, namely 3 months and 6 months after the first injury. Sensitivity of peripheral nociceptive neurons and central underlying the process of transition from acute pain to chronic pain. There are several factors that influence the increasing incidence of postoperative chronic pain including preoperative, intraoperative and postoperative factors. Untreated acute postoperative pain also increases the risk of increasing chronic postoperative pain. In Asia, the prevalence of chronic pain varies widely, between 7% in Malaysia to 60% in Cambodia. The prevalence of postoperative chronic pain in adults is reported to be around 20% in developed countries. The incidence includes all ages with a higher incidence in women and the elderly. The purpose of this study was to describe the characteristics of postoperative chronic pain in outpatients in the surgical polyclinic and obstetrics and gynecology polyclinic at RSU Medan. The type of research used in this study was Observational with a Cross Sectional method approach. Based on the research that has been done, it was found that ages 26-35 years experienced the most chronic pain, namely as much as 29.8% and women experienced more chronic pain compared to men. Based on this study it was found that the majority of respondents experienced moderate pain intensity as many as 36 respondents (63.2%). There were descriptions of characteristics that were mostly 26-35 years old.